How Learning a Musical Instrument Affects the Development of Skills - Adrian Hille; Jürgen Schupp (Economics of Education Review, 2015)
Despite numerous studies on skill development, we know little about the effects of extracurricular music activities on cognitive and non-cognitive skills. This study examines how music training during childhood and youth affects the development of cognitive skills, school grades, personality, time use and ambition using data from the German Socio-Economic Panel (SOEP). Our findings suggest that adolescents with music training have better school grades, are more conscientious, open and ambitious. These effects are stronger among adolescents from lower socio-economic status. In order to address the non-random selection into playing music, we take into account detailed information on the child and its parents, which may determine both the decision to pursue music lessons and educational outcomes. While lacking truly exogenous variations in music activities, our results are robust to a large range of sensitivity tests. We thereby approach causality better than previous observational studies.
Additional information: NOTICE: This is the author's version of a work that was accepted for publication in Economics of Education Review. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Economics of Education Review 44 (2015), pp. 56-82 and is online available at http://dx.doi.org/10.1016/j.econedurev.2014.10.007.
Keywords: I21; J24; Z11; 330; Music; Cognitive and non-cognitive skills; Educational achievement; SOEP; Musik; Bildungsertrag; Panel; Deutschland